2014
DOI: 10.3791/51208
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Serotyping of <em>Streptococcus pneumoniae</em> Using the Quellung Reaction

Abstract: There are over 90 different capsular serotypes of Streptococcus pneumoniae (the pneumococcus). As well as being a tool for understanding pneumococcal epidemiology, capsular serotyping can provide useful information for vaccine efficacy and impact studies. The Quellung reaction is the gold standard method for pneumococcal capsular serotyping. The method involves testing a pneumococcal cell suspension with pooled and specific antisera directed against the capsular polysaccharide. The antigen-antibody reactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 21 publications
(22 reference statements)
0
51
0
1
Order By: Relevance
“…These are most likely negative reactions. In such cases, we recommend retesting and/or further investigation using another serotyping method (for example the Quellung reaction 17 ). …”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are most likely negative reactions. In such cases, we recommend retesting and/or further investigation using another serotyping method (for example the Quellung reaction 17 ). …”
Section: Representative Resultsmentioning
confidence: 99%
“…Serotyping a pneumococcal isolate by latex agglutination takes approximately 10 min, and up to four latex reagents can be tested in parallel on the one slide. Furthermore, if the prevalence of serotypes is known for the relevant epidemiological setting, testing can be performed in rounds starting with the pools containing the most common serotypes similarly to the Quellung test 17 . This approach minimizes the number of tests needed to determine the serotype.…”
Section: Discussionmentioning
confidence: 99%
“…Equivocal reactions were confirmed using the Quellung reaction with antisera from SSI [25]. Isolates that were non-typeable were tested for the presence of the lytA gene by real-time PCR [26].…”
Section: Methodsmentioning
confidence: 99%
“…It 131 is also inconvenient for serotyping large number of isolates and is rela-132 tively laborious and costly as it requires a supply of pneumococcal 133 antisera. To improve the latter, Habib and colleagues (Habib et al,134 2014) developed an improved Quellung protocol that minimizes the 135 amount of antisera used (Habib et al, 2014) (a video for the protocol 136 is also available at http://www.jove.com/video/51208/). This is done (Christensen et al, 1973;Kronvall, 1973;Lund and 154 Rasmussen, 1966;SSI, 2012).…”
mentioning
confidence: 99%
“…The described agglutination method is a break-through 169 due to its accuracy, rapidity and the significant reduction of antiserum 170 used compared to the Quellung reaction(Porter et al, 2014). blot(Fenoll et al, 1997) and colony blot assays(Bogaert et al, 173 2004) have been suggested as alternatives to the Quellung reaction as 174 faster and less expensive methods for pneumococcal typing.…”
mentioning
confidence: 99%